Colloidal Perspective on Targeted Drug Delivery to the Central Nervous System - Wang, Wenqian (Langmuir : the ACS journal of surfaces and colloids, 2023)
This article describes a new approach in targeted drug delivery to the central nervous system (CNS) in a significant departure from the predominant systematic drug administration attempting to penetrate the blood-brain barrier (BBB). Nanoparticles chemically conjugated to neural tract tracer proteins are capable of path-specific axonal retrograde transport, transneuronal transport, and anatomical tract flow to bypass the BBB. To celebrate the work by Dr. Bettye Washington Greene on the physical chemistry of colloidal particles, this article focuses on the physiochemical characteristics of the nanoparticles, various colloidal forces that impact the colloidal stability of nanoparticles in biological media, and surface chemistry strategies to avoid nanoparticle aggregation-induced poor therapeutic outcomes. The biological environment for the anatomical retrograde transport of neural tract tracers is examined to directly link factors impacting the colloidal stability of the new class of CNS-targeting nanoconjugates such as nanoconjugate size, shape, surface charge, surface chemistry, ionic strength, pH, and protein adsorption on the nanoparticle. We conclude with opportunities and challenges for future research